Revitalization of Sumenep Regency's Traditional Games as Cultural Heritage and Their Relevance to Character Education in Schools - Moh. Lutfi (Civiliza Publishing, Indonesia., 2025)
Traditional games are a part of cultural heritage that contain noble values and can serve as an effective medium for character education. This article aims to identify the development, character values, and revitalization strategies of traditional games in Sumenep Regency, as well as their relevance to character education in schools. The research method used is a qualitative descriptive method with a literature review approach, utilizing various sources such as books, journals, and scientific articles as the primary objects. The results show that traditional games are facing challenges from technological advancements, which are gradually shifting their role. Sumenep’s traditional games contain values such as gotong royong (mutual cooperation), honesty, sportsmanship, leadership, and creativity, which are relevant to the character building of the younger generation. There are several strategies for revitalizing traditional games, including the processes of internalization, socialization, enculturation, and inheritance. The complexity of character education values found in traditional games is highly relevant to educational goals.